Opening to God : lectio divina and life as prayer - Benner, David G. (Downers Grove, Ill. : IVP Books, 2010)
Spiritual director David Benner invites us to discover openness to God as the essence of prayer, spirituality and the Christian life. Prayer is far more than saying words to God; all of life can be prayer when offered to God in faith and with openness. Using the four movements of lectio divina, Benner explores prayer as attending, pondering, responding and being. Along the way he opens us to a world of possibilities for communion with God: praying with our senses, with imagination, with music and creativity, in contemplation, in service and much more.--from publisher's description.
Introduction : transforming openness to God -- More than you can imagine -- Preparing for the divine encounter -- Lectio divina and four classic prayer paths -- Prayer as attending -- Prayer as pondering -- Prayer as responding -- Prayer as being -- Life as prayer, prayer as life -- Transformation prayer.
Includes bibliographical references.
Description based on print version record.
Keywords: Bible -- Devotional use; Prayer -- Christianity; Spiritual life -- Christianity; RELIGION / Christian Life / General; Electronic books